Low-Level Laser Therapy including Laser Acupuncture for Non-Specific Chronic Low Back Pain: Systematic Review and Meta-Analysis - Hyewon Yeum; Yejin Hong; Dongwoo Nam (MEDrang Inc., 2021)
Low-level laser therapy including laser acupuncture (LLLT/LA) has been widely used for non-specific chronic low back pain (NCLBP). However, there is no critically appraised evidence of its potential benefits. This study aimed to evaluate the effectiveness of LLLT/LA for NCLBP. There were 12 databases (MEDLINE, CENTRAL, EMBASE, KoreaMed, KMBASE, KISS, NDSL, KISTI, OASIS, CNKI, CiNII, J-stage) searched for randomized controlled trials using LLLT/LA for NCLBP up until June 2019. The primary outcome was pain intensity and functional status/disability due to NCLBP. A random-effects meta-analysis was conducted on 20 studies involving 1,323 participants. LLLT/LA showed a significant positive effect on pain relief scores compared with sham treatments (SMD −0.51, 95% CI: −0.88 to −0.13; χ2 = 31.12, I2 = 74%). Alone, the therapy showed a significant positive effect on function/disability scores (30 participants, MD −11.90, 95% CI: −17.37 to −6.43). As an add-on treatment, it showed a significant positive effect on pain relief (80 participants, MD −5.10, 95% CI: −9.31 to −0.88; χ2 = 28.99, I2 = 97%) and improved function/disability scores (120 participants, MD 5.44, 95% CI: 2.19 to 8.68; χ2 = 4.07, I2 = 75%). Among 20 studies, 9 studies reported no adverse events and 1 study reported mild adverse events. LLLT/LA may be an alternative or add-on treatment for NCLBP.